Trastornos afectivos y su incidencia en el rendimiento académico de los estudiantes de la escuela de educación básica Paul Percy Harry Bryan de la ciudad de Machala perteneciente a la ciudadela el bosque. - Paladinez Velez, Merci Yolanda (2015)
This research in the educational process is reflected, it is set to present affective disorders and how they affect the academic performance of students of the school Harry Percy Paul Bryan, which significantly interfere the intellectual achievement of students at the different subjects taught at the school, indicating the intervention as a fundamental part of the family, teachers and students that with their help it was possible that students who were in this situation may improve performance academic since they were motivated by the involvement of parents, teachers and other students, practicable methods and strategies in the process of guiding students to present their different situations for your help.